Octavia Hill, social activism and the remaking of British society - Baigent, Elizabeth; Cowell, Ben (IHR Conference Series, 2016)
This volume reassesses the life and work of Octavia Hill, housing reformer, open space campaigner, co-founder of the National Trust, founder of the Army Cadet Force, and the first woman to be invited to sit on a royal commission. In her lifetime, if not a household name, Octavia Hill was widely regarded as an authority on a broad range of acknowledged social problems, particularly housing and poverty. Yet despite her early pre-eminence, subsequent attempts by family members to keep her memory alive, and the remarkable success of the institutions which she helped to found, Hill fell from public favour in the twentieth century. The fourteen chapters in this book will help to provide a more nuanced portrait of Hill and her work in a broader context of social change, reflecting recent scholarship on nineteenth-century society in general, and on philanthropy and preservation, and women's role in them, in particular.